Utilization of Social Media by Farming Community: A Case from Punjab State - Joshi, Divyata; Dhaliwal, RK (Indian Journal of Extension Education, 2021)
To equip the farmers with recent technologies and innovations, various tools of cyber extension are being used by the farming community, social media is one such area. To understand the utilization pattern of these social media tools used by farmers for agricultural purpose, the study was conducted in Punjab state with 50 respondents selected by simple random sampling. The data were collected through structured interview schedule. Two-thirds of the respondents (66%) used YouTube always for agriculture-related information. 52% used PAU Kisan App sometime, whereas 34% used  always for getting agriculture information. majority (58%) of the farmers posted queries on social media platforms. 68 per cent of the farmers contribute to discussions held in social media. TwoÂ third of the respondents (66%) shared agriculture information further on social media. Most of the farmers (74%) said that social media fulfills their information needs. The majority used social media for seeking informationÂ related to agriculture such as new varieties, training etc. Hence, it can be concluded that social media can be a new age solution to cater to the challenge of less availability of extension personnel by complementing the personnel for quick and effective dissemination of agriculture-related information, ultimately empowering farming community.